(untitled) (American Journal of Pedagogical and Educational Research, 2026)
The present study examines the linguistic conceptualization of the notions “man” and “woman” in Spanish phraseological units. Phraseology is approached as a culturally saturated domain of language that reflects collective representations, social values, and evaluative stereotypes (Corpas Pastor, 1996; Sabban, 2008). The material comprises gender-marked idioms and fixed expressions drawn from authoritative phraseological dictionaries and corpus data. Using a combination of semantic, conceptual, and comparative methods, the analysis identifies the dominant semantic fields and axiological components associated with masculinity and femininity. The results reveal a systematic asymmetry: phraseological units referring to men predominantly encode attributes of strength, agency, rationality, and social authority, whereas those associated with women tend to emphasize appearance, emotionality, morality, and socially regulated behavior (Hellinger & Bußmann, 2001–2003; Talbot, 2010). The study demonstrates that Spanish phraseology contributes to the preservation and transmission of traditional gender models within the linguistic worldview.